Keith Sonnier - until today - Grove, Jeffrey D. 1962- (Parrish Art Museum, 2018)
One of the first artists to use light, specifically neon, as a form of sculpture, Keith Sonnier changed our ideas of what sculpture is and could be. From his early pieces such as Rat Tail Exercise and the Ba-O-Ba series to his most recent luminous neon-based series, this book explores the progression and influence of Sonnier's oeuvre. Essays in the book look at Sonnier's numerous public art projects, including a kilometer-long installation at the Munich airport, his relationship with his native Louisiana culture, and the architectural influences in his work. One of the art world's most productive figures, Sonnier continues to redefine the parameters of sculpture. This beautiful monograph celebrates an artist who has never ceased experimenting-and never stopped astonishing his audience. Exhibition: Parrish Art Museum, Water Mill, USA (1.7.2018 - 27.1.2019)
Impressum: Published in conjunction with the exhibition: "Keith Sonnier: until today" Parrish Art Museum, New York, July 1, 2018-January 27, 2019, New Orleans Museum of Art, New Orleans, March 15-June 2, 2019
Keywords: Sonnier, Keith -- 1941-2020; Sonnier, Keith / 1941- / Exhibitions; Sonnier, Keith / 1941- / Interviews; Sculpture / Exhibitions; Neon lighting in art / Exhibitions; Bildband; Ausstellungskatalog -- Parrish Art Museum -- 01.07.2018-27.01.2019 -- Water Mill, NY; Ausstellungskatalog -- New Orleans Museum of Art -- 15.03.2019-02.06.2019 -- New Orleans, La.